Regional difference in the EMG-force relationship of the hamstring muscles during knee flexion - Raki Kawama; Hirohiko Maemura; Satoru Tanigawa (Japanese Society of Physical Fitness and Sports Medicine, 2021)
The relationship between electromyographic (EMG) amplitude and exerted force has been established in numerous studies and used as fundamental knowledge to interpret the results of EMG in human movement. Recent neuroanatomical studies suggest that the individual hamstring muscles may be regionally regulated by the central nervous system. In fact, a few studies observed nonuniform EMG activities between regions along the length of the biceps femoris long head (BFlh) and semitendinosus (ST) during knee flexion exercise. However, it remains unknown whether the EMG-force relationship varies among regions of the individual hamstring muscles. This study aimed to compare the EMG-force relationship among regions of the individual hamstring muscles during knee flexion exercise. Thirteen healthy males performed isometric knee flexion at 20%-80% of maximal voluntary contraction (MVC). Surface EMG amplitudes in the proximal, middle, and distal regions of the biceps femoris long head, semitendinosus, and semimembranosus (SM) were assessed and normalized to the root mean square (RMS) during MVC as %RMS. The results showed that %RMS of BFlh was consistently higher in the distal regions than in the proximal region at 20%-80% of MVC (all: p < 0.05). In ST, %RMS in the middle and distal regions were higher than that in the proximal regions only at 20% of MVC (p < 0.05). Similarly, %RMS of SM was higher in the middle region than in the proximal region at 20% and 40% of MVC (all: p < 0.05). These results suggest that the EMG-force relationship is not consistent among regions of the individual hamstring muscles, especially between the proximal and distal regions of BFlh.